Application of a pre-emptive question and answer platform to improve the level of satisfaction during family meetings in general medical wards - Wen-Chun Yu; Chun-Ta Huang; Wang-Huei Sheng (BMC, 2022)
Abstract Background A successful family meeting is key to family-centered care and may foster communication and improve the level of satisfaction of the family in terms of communication. In this study, we evaluated whether a proactive communication channel could improve the level of satisfaction of family members following a family meeting in a general medical ward setting. Methods We conducted a pre- and post-study to compare the level of satisfaction of a family with a family meeting before (N = 39) and after (N = 29) intervention in two general medical wards of a tertiary-care referral center. The intervention included a pre-emptive question and answer platform and a written response to family-raised queries in addition to a regular setting. Following each family meeting, family members were requested to fill a 10-item survey assessing their levels of satisfaction. Results The characteristics of the family members in terms of demographics, education levels, and previous experiences with family meetings in the pre- and post-intervention groups were similar. The scores in all the items that indicated the level of satisfaction significantly improved after intervention. The overall score for satisfaction increased from 85 (interquartile range, 80-95) to 98 (interquartile range, 93-100; P < 0.001). Conclusions Compared with conventional practice, the inclusion of a proactive communication platform along with a written response to raised queries as a part of family meetings improved the satisfaction levels of the family in terms of the content and process of the meeting in the general ward setting. Further studies are needed to delineate the optimal timing and use of such a communication modality.